Tratamento físico-químico em efluente de vinícola de pequeno porte - Lechinhoski, Maryelen (2015)
The organic matter present on those winery effluents varies from 1.200 mg.L-1 to 92.000 mg.L-1 of COD. The pH is acidic, varying from 3,5 to 5,0. The concentration of phenolic compounds ranges between 41 to 1450 mg.L-1 C6H5OH . For ammonia the concentration varies from 12 to 208 mg.L-1. Sulfates have to between 50 and 500 mg.L-1 S. Based on these information, a physical-chemical treatment system was proposed, analyzed into batches, which consisted of the advanced Fenton ́s Oxidation and two adsorption columns filled with alternated adsorbents: one with pottery residues and the other with residues from building (concrete) sites ( crushed on crushing machines). The winery effluent characterization was establish according to the following parameters: pH, turbidity, COD, solids, nitrogen, phosphate and phenols. The absorbents resources were characterize pH, bulk and relative densities, moisture content, volatile material, ash content. The assays begun with the oxidation of the raw effluent, followed by the addition of 16 g.L-1 of hydrogen peroxide related to a COD of z=3,36 (H2O2/DQO). Ferrous sulfate catalyzed the reaction at 1:15 portion (FeSO4.7H2O:H2O2), on an agitated platform at 150 rpm for four hours at 30oC. Once Fenton’s oxidation was concluded, the effluent was applied to the pottery absorption column, at 5m3/m2.day-1, and subsequently applied to the building sites residues column at 4m3/m2.day-1. The system’s performance was evaluate according to the COD, turbidity, nitrogen, solids, phenols and color. The COD efficiency removal obtained was 92,25%, reaching COD values of 369 mg.L-1. In addition, the chosen applied treatment revealed to be efficient on the elimination of color (100%), phenols (100%), turbidity (100%), sulfates (98%) reaching a concentration of 40.5 mg.L-1, nitrogen (10%) with 17.25 mg.L-1, and on solids removals: ST (95% with values of 2,29 mg.L-1), STF (71% and 0,92 mg.L-1), STV (97% and 1,37 mg.L-1), SST (95% and 0,08 mg.L-1), SSF (96% and 0,01 mg.L-1), SSV (91% and 0,09 mg.L-1), SDT (95% and 2,21 mg.L-1), SDF (67% and 0,9 mg.L-1) e SDV (97% and 1,27 mg.L-1). The advantage of the Fenton application on the raw effluent consisted on taking benefit of the acidic environment of the effluent, environment that gave the right condition to avoid the precipitation of the iron sulfate, becoming the reaction catalyst. Once the oxidation was completed, it was necessary to neutralize de pH to allow the iron precipitation, which took place into the building residues adsorption columns, allowing iron the precipitation, filtration and removal. These methods combined enabled and minimized the use of chemical reagents, allowing it to be easily mounted in wineries with seasonality production and wineries without a large area to install bigger and more complex systems. In conclusion, the physical – chemical system proposed revealed to be efficient on the removal of the organic mass, colors, solids, nitrogen, sulfates and phenols, allowing the discharge of effluent disposal.